An In-Person and Telemedicine "Hybrid" System to Improve Cross-Border Critical Care in COVID-19. Issue 1 (4th January 2021) - Ramnath, Venktesh R.; Hill, Linda; Schultz, Jim; Mandel, Jess; Smith, Andres; Morris, Tim; Holberg, Stacy; Horton, Lucy E.; Malhotra, Atul; Friedman, Lawrence S.
Background: UC San Diego Health System (UCSDHS) is an academic medical center and integrated care network in the US-Mexico border area of California contiguous to the Mexican Northern Baja region. The COVID-19 pandemic deeply influenced UCSDHS activities as new public health challenges increasingly related to high population density, cross-border traffic, economic disparities, and interconnectedness between cross-border communities, which accelerated development of clinical collaborations between UCSDHS and several border community hospitals – one in the US, two in Mexico – as high volumes of severely ill patients overwhelmed hospitals. Objective: We describe the development, implementation, feasibility, and acceptance of a novel critical care support program in three community hospitals along the US-Mexico border. Methods: We created and instituted a hybrid critical care program involving: 1) in-person activities to perform needs assessments of equipment and supplies and hands-on training and education, and 2) creation of a telemedicine-based (Tele-ICU) service for direct patient management and/or consultative, education-based experiences. We collected performance metrics surrounding adherence to evidence-based practices and staff perceptions of critical care delivery. Findings: In-person intervention phase identified and filled gaps in equipment and supplies, and Tele-ICU program promoted adherence to evidence-based practices and improved staff confidence in caring for critically ill COVID-19 patients at each hospital. Conclusion: A collaborative, hybrid critical care program across academic and community centers is feasible and effective to address cross-cultural public health emergencies.